Enhancing Learning Motivation of Special Needs Children through Arts and Skills Approaches - Juliandari, Jihan; Fitriani, Wahidah; Yeni, Putri; Zahir, Roya (Darussalam: Journal of Psychology and Educational, 2024)
Education plays a crucial role in a child's life, aiming to help them develop abilities through classroom learning. Motivation is a key factor in achieving educational goals, significantly impacting students' performance, including those with special needs in inclusive education. In Indonesia, inclusive education policies ensure equal educational opportunities for all, including special needs children. This research explores how creative skills can enhance the learning motivation of special needs children at SLB Negeri 1 Pagaruyung. Utilizing qualitative methods, the study observes classroom interactions and interviews teachers to understand effective teaching methods and challenges. Findings indicate that creative activities, such as crafts and poetry, significantly boost motivation and confidence in special needs students. Teachers play a vital role in identifying and nurturing students' talents through continuous support and positive reinforcement. The study emphasizes the importance of innovative teaching approaches and a supportive learning environment in fostering motivation and personal growth among special needs children. These insights contribute to developing effective strategies for inclusive education, ensuring all children can reach their full potential.